(untitled) (Research, Society and Development, 2024)
This research had the general objective of critically analyzing the current scientific literature on the challenges faced in obstetric surgery and the solutions proposed to reduce complications and improve maternal and fetal outcomes. The methodological proposal used consists of an integrative review of the literature, constructed through a survey of data in scientific databases: PubMed, Scopus and Web of Science. The integrative review highlighted a variety of challenges in obstetric surgery, including complications during childbirth and the high rate of unnecessary cesarean sections, directly threatening maternal and fetal life. Solutions emerged, such as multidisciplinary approaches, technological advances and complication prevention strategies. Additionally, ongoing education and equitable access to obstetric care have been identified as essential to improving outcomes. However, persistent gaps in knowledge and socioeconomic and cultural challenges require future research and comprehensive health policies to ensure the safety and quality of obstetric care on a global scale. Thus, the results highlighted the variety of challenges, such as complications during birth and a high rate of unnecessary cesarean sections, which directly impact maternal and fetal outcomes. However, several potential solutions have also been identified, including multidisciplinary approaches, technological advances, educational programs, and complication prevention strategies, that have the potential to significantly improve the safety and quality of obstetric care.